Narrowing communication gaps in teaching international students - Mohd Faiz, Nur Sofurah; Awang, Halizah; Mohamed, Maziana (Universiti Putra Malaysia Press, 2017)
Research into the adjustment experiences of international students in higher education institutions has been undertaken over the past 50 years. In the related literature, much of the discussion has focussed on academic challenges that international students have encountered during their transition. Debate has also centred on the methods of support that academic staff could provide to assist the transition of international students. This paper highlights the findings of a case study on pedagogical approaches of academic staff in a Malaysian Technical University in narrowing communication gaps when teaching international students. Nine academic staff were interviewed to explore their experiences on communication challenges in the classroom and methods they implemented in encountering those issues. Findings illustrated that low English proficiency was the most significant challenge these staff encountered in teaching international students, and two specific pedagogical approaches were implemented in assisting this issue, namely, (i) using simple English with teaching aids, and (ii) teaching in two languages were. These methods were perceived to have assisted not just the learning of international students, but also to have narrowed communication gaps between the students and academic staff